Penerapan Model Pembelajaran Advance Organizer Terhadap Pemahaman Konsep Siswa Pada Materi IPA Fisika Kelas VIII di SMPN 02 Sintuk Toboh Gadang, Padang Pariaman - Aswirna, Prima; putri, tesalia (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2017)
This research The problem inthis research is how the understanding of the concept of students in learning physiscs class VIII SMPN 2 Sintuk Toboh Gadang by applying advance organizer learning models. As for the purpose to be achieved in this research is : 1) to find out how to comprehed the concept of students in learning physiscs using advance organizer learning models. 2) to know the learning activities of students with advance organizer learning models. This research is quantitative research through quasi experiment method with post-test design only control group design. Population in this study were students of class VIII Junior Hight School 2 Sintuk Toboh Gadang, Padang Pariaman City. Determination of sample by rondom sampling technique with class VIII.1 as experiment class and class VIII.3 as control class which each have 35 students. Data collection techniques using tests. The validity used is the correlation of the person showing the instrument is valid. Before the data analysis, first tested normality and homogeneity test and data analysis techniques used are test-t.The results of this study indicate a difference understanding of the concept of class VIII students in Junior Hight School 2 Sintuk Toboh Gadang using advance organizer learning models compared with the direct model. The difference is indicated by t-test results with the help of SPSS 20. T-test score shows the number 4,125 tith df = 68 then t tabel = 2,142 then t arithmetic of t tabel and sig value 0.000 < 0.05 which proves that experiment class learning is better than control class learning.